Soekarno's Political Attitude Towards the Masjumi Party 1957-1960 as a Learning Resource for History Subjects - Ahmad, Zaini Muslim (Indonesian Journal of History Education, 2017)
The purpose of this study was (1) to understand the political attitudes of Sukarno in overcoming political gridlock, (2) to understand the Party's attitude towards Soekarno Masjumi during Guided Democracy, (3) to know Masyumi's reaction to changes in Sukarno 'ss political attitudes. The research method is the historical method, which goes through the steps of heuristic, source criticism, interpretation, and writing of history or historiography. The results of the study concluded the following: (1) Soekarno's attitude in overcoming political gridlock was by issuing a Presidential Decree that was declared on July 5, 1959, back to 1945; the decree is also the starting point to show the passing of Sukarno's Guided Democracy as an authoritarian leader. (2) Party Masjumi, considered by Soekarno as a counterrevolutionary group, often gets 'castration of politics" and is finally dissolved by Presidential Decree No 7/1959 and Presidential Decree No.200/1960. (3) Party Masjumi responds to the changing political attitudes of Soekarno by always showing opposition to Sukarno's measures, policies, and leadership.